2015
DOI: 10.1038/ncb3130
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible TAp73 supports tumorigenesis by regulating the angiogenic transcriptome

Abstract: The functional significance of the overexpression of unmutated TAp73, a homologue of the tumour suppressor p53, in multiple human cancers is unclear, but raises the possibility of unidentified roles in promoting tumorigenesis. We show here that TAp73 is stabilized by hypoxia, a condition highly prevalent in tumours, through HIF-1α-mediated repression of the ubiquitin ligase Siah1, which targets TAp73 for degradation. Consequently, TAp73-deficient tumours are less vascular and reduced in size, and conversely, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 52 publications
(47 reference statements)
5
79
0
1
Order By: Relevance
“…Overall, independent groups have consistently reported opposite roles for TAp73 and DNp73, respectively, in repressing and promoting angiogenesis. Conversely, a fourth group identified a new E3 ubiquitin ligase, Siah1 (seven in absentia 1), that is able to degrade TAp73 following its regulation by HIF-1a [32], adding a further level of complexity to the p73/HIF interaction. Intriguingly, however, a relevant proangiogenic HIF-1a effect seems to be mediated by TAp73, at least in E1-Ras transformed MEFs.…”
Section: Reviewmentioning
confidence: 99%
“…Overall, independent groups have consistently reported opposite roles for TAp73 and DNp73, respectively, in repressing and promoting angiogenesis. Conversely, a fourth group identified a new E3 ubiquitin ligase, Siah1 (seven in absentia 1), that is able to degrade TAp73 following its regulation by HIF-1a [32], adding a further level of complexity to the p73/HIF interaction. Intriguingly, however, a relevant proangiogenic HIF-1a effect seems to be mediated by TAp73, at least in E1-Ras transformed MEFs.…”
Section: Reviewmentioning
confidence: 99%
“…In essence, clinical samples obtained with SingHealth Centralized Institutional Review Board B ethics approval were used for p53EII transcript analyses and determination of p53 mutation status by standard sequencing and PCR, and also for immunoblot and immunohistochemical analyses, as described in detailed in SI Appendix. All cell culture and biochemical work, transfections, target gene analysis by quantitative real-time PCR, and chromatin immunoprecipitations were performed as described (28,38,39).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, protein-protein interaction prediction showed that vascular endothelial growth factor receptor (VEGF-R) was altered, which may play a vital role in the regulation of SIV formation (Supporting Information, Figure S1F). Figure 2A showed the identified 72 different angiogenic genes with 21 up-regulated and 51 down-regulated after treatment with vehicle control (0.1% DMSO) or EriB (10 and 15 μM) for 72 h using a cut-off point (p < 0.05) and method described in the materials and methods section [28]. Results showed that the expressions of significantly altered genes (Fold-change > 2) were consistent with the alterations from transcriptome profiling validated by Real-time PCR (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…The differentially expressed genes were analyzed in the Database for Annotation, Visualization and Integrated Discovery (DAVID), which could identify the Gene Ontology (GO) terms and KEGG pathway maps. The angiogenesis related genes were identified according to GO enrichment analysis and Angiogenic Growth Factors RT 2 Profiler PCR Array (SABiosciences, Frederick, MD, USA) [28]. …”
Section: Methodsmentioning
confidence: 99%